Hubungan Perubahan Iklim dengan Ketahanan Petani Tembakau di Kabupaten Bojonegoro, Indonesia - Ma’arif, Zaenul; Sueadi, Falih; Pandin, Moses Glorino Rumambo (Academy of Education Journal, 2025)
Climate change is a global issue that has a significant impact on the agricultural sector, including tobacco commodities in Bojonegoro Regency as the main producer of Virginia tobacco in East Java. This study aims to analyze the relationship between climate change risks and the resilience index of tobacco farmers, with a focus on identifying risk forms, measuring resilience based on five capitals (natural, human, physical, financial, social), and the dominant factors that influence resilience. The research method uses a quantitative explanatory approach through a questionnaire to 436 tobacco farmers in five production center districts (Kepohbaru, Baureno, Kedungadem, Sumberrejo, Kanor), selected by stratified random sampling. Data analysis was carried out using Structural Equation Modeling-Partial Least Squares (SEM-PLS) and mediation tests. The results of the study indicate: climate change risks (managed with the SHARP/FAO approach) have a significant effect on farmer resilience; Productive factors (business efficiency), resilience (ability to survive), and human (adaptive capacity) are positively related to resilience; Social factors (networks, community support) have a negative relationship, indicating that weak social networks have the potential to reduce resilience. Adaptive factors have no direct effect, but are significant through mediation of adaptation strategies and access to information. This study found that increasing tobacco farmer resilience requires structured interventions that address access to climate information, adaptation training, and strengthening human capital and productivity. Policy implications include the development of a climate early warning system, business diversification, and farmer group-based mentoring to reduce social vulnerability.